ORGANIZATIONAL COMMITMENT AMONG PRIVATE SECTOR WORKERS IN ANAMBRA STATE, NIGERIA: A CORRELATION OF PAY SATISFACTION - Joe-Akunne, Chiamaka; Ezeh, Leonard N (Practicum Psychologia, 2019)
The study examined the relationship between pay satisfaction and organizational commitment among private sector workers in Anambra State, Nigeria. Two hundred and thirty-two (232) participants comprising 115 males and 117 females aged between 17 – 60 years with a mean age of 29.72 years and standard deviation of 6.82 participated in the study. Two instruments were used: Pay Satisfaction Questionnaire (Heneman and Schwab, 1985), and the Organizational Commitment Questionnaire (Meyer and Allen, 1993). One hypothesis was tested in the study. It stated that pay satisfaction will have a significant relationship with organizational commitment among employees of private organizations and it was accepted at (r = .18, p<.00). Hence the study concluded that satisfaction with pay increases employees’ commitment in an organization.